LIDAH TAK BERTULANG NAMUN TAK TERKUASAI Kajian Hermeneutik Kritik Historis Terhadap Teks Yakobus 3:1-12 dan Implikasinya Bagi Pemuda Jemaat GMIM Viadolorosa Kairagi II - Talu, Siselia Jacobna; Tewu, Peggy S. (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
This research aims to explain the interpretation made of the text James 3:1-12. The aim of this research is to explore the meaning of a boneless but uncontrolled tongue according to James 3:1-12 and explain it to readers and young people, strengthened theologically by James 3:1-12. In conducting this research, we used a research approach to literature, in this case we wanted to carry out interpretive or hermeneutic work on a text and we chose to use a historical critical approach. The results of this research are theological points about a boneless but uncontrolled tongue being a sin of a teacher's responsibility, warnings regarding the use of the tongue, blessings and curses should not come out of the same mouth. The meaning of this theology is implied for the youth of the GMIM Viadolorosa Kairagi Dua congregation to be able to maintain speaking ethics as young Christians